Data from: Size‐dependent stress response in juvenile Arctic charr (Salvelinus alpinus) under prolonged predator conditioning - Kortet, Raine; Laakkonen, Mika V.M.; Tikkanen, Jouni; Vainikka, Anssi; Hirvonen, Heikki (Zenodo, 2019)
Predator conditioning can be used to improve post-release antipredator recognition of hatchery-reared salmonids. However, possible negative stress-related effects of prolonged predator conditioning on juvenile fish physiology are poorly understood. We studied the effects of prolonged (91 days) predator odour exposure on whole-body cortisol level and spleen size in six full-sib families of juvenile hatchery-bred Arctic charr (Salvelinus alpinus). Chemical cues from water containing charr-fed pikeperch (Sander lucioperca) were used as the predator exposure stimuli, and lakewater was used as a chemical control. Our study revealed that juvenile body cortisol levels post-predator conditioning were affected by treatment, fish size and their interaction. Importantly, among the smaller (i.e. slowest growing) charr, the predator-exposed fish had higher cortisol levels than control fish, while the opposite pattern was true for the larger fish. These results suggest that chemical cues from charr-fed predators induce a prolonged stress response in juvenile charr. As prolonged predation exposure seems to elevate stress levels in a size-dependent manner, the larger, faster growing fish could possibly have intrinsically lower stress responses to predation threats than smaller, slower growing fish. Possible coupling between stress sensitivity and growth requires further attention due to the likely implications for the management of unintended domestication among captive-reared salmonids. Arctic_charr_cortisol_data_Dryad Cortisol data